From Shtetl to Stardom : Jews and Hollywood - Ansell, Lisa; Brook, Vincent, 1946-; Renov, Michael, 1950-; Ross, Steven J. (Steven Joseph) (Jewish role in American life ;, 2016)
The influence of Jews in American entertainment from the early days of Hollywood to the present has proved an endlessly fascinating and controversial topic, for Jews and non-Jews alike. From Shtetl to Stardom: Jews and Hollywood takes an exciting and innovative approach to this rich and complex material. Exploring the subject from a scholarly perspective as well as up close and personal, the book combines historical and theoretical analysis by leading academics in the field with inside information from prominent entertainment professionals. Essays range from Vincent Brook's survey of the stubbornly persistent canard of Jewish industry "control" to Lawrence Baron and Joel Rosenberg's panel presentations on the recent brouhaha over Ben Urwand's book alleging collaboration between Hollywood and Hitler. Case studies by Howard Rodman and Joshua Louis Moss examine a key Coen brothers film, A Serious Man (Rodman), and Jill Soloway's groundbreaking television series, Transparent (Moss). Jeffrey Shandler and Shaina Hamermann train their respective lenses on popular satirical comedians of yesteryear (Allan Sherman) and those currently all the rage (Amy Schumer, Lena Dunham, and Sarah Silverman). David Isaacs relates his years of agony and hilarity in the television comedy writers' room, and interviews include in-depth discussions by Ross Melnick with Laemmle Theatres owner Greg Laemmle (relative of Universal Studios founder Carl Laemmle) and by Michael Renov with Mad Men creator Matthew Weiner. In all, From Shtetl to Stardom offers a uniquely multifaceted, multimediated, and up-to-the-minute account of the remarkable role Jews have played in American movie and TV culture.